Social responsibility, corporate giving and the tide. Issue 9 (17th October 2016) - Catalão-Lopes, Margarida; Pina, Joaquim P.; Branca, Ana S.
Abstract : Purpose: The purpose of this paper is to address firms' decisions on corporate social responsibility (CSR) as a function of the economic environment. The paper focuses on corporate giving, a CSR dimension that is especially important in an economic downturn such as the one experienced by many European economies since 2007-2008. Design/methodology/approach: A theoretical framework comprising product differentiation and market competition is proposed. The paper investigates whether adverse economic conditions refrain corporate giving or, alternatively, stimulate it as a differentiation and demand enhancing instrument. Econometric empirical testing on the business cycle properties of giving at an aggregate level is also conducted. Findings: According to theoretical results, firms seem to refrain giving under adverse economic conditions in the short run. Empirically, the paper concludes for a pro cyclical contemporaneous relation of corporate giving with real gross domestic product, supporting the theoretical finding. In a dynamic perspective, however, giving causes revenues and firms tend to donate more than a few years after the downturn. Originality/value: The paper examines the behaviour of an under researched component of corporate social responsibility, which is especially important in economic downturns - giving. It considers continuous degrees of market competition and differentiation.